Enrolling girls without learning: Evidence from public schools in Afghanistan - Asadullah, M. Niaz; Alim, Md. Abdul; Hossain, M. Anowar (Wiley Online Library, 2022)
This article was published in the Development Policy Review [© The Authors 2017. Development Policy Review © 2017 Overseas Development Institute] and the definite version is available at: https://doi.org/10.1111/dpr.12354 The Article's website is at: https://onlinelibrary.wiley.com/doi/ftr/10.1111/dpr.12354